How is Fintech Lending Transforming Traditional Banking Systems Globally? A Literature Review Analysis (International Journal of Economics Management and Social Science, 2026)
The emergence of financial technology (fintech) lending platforms has fundamentally transformed the global financial services landscape, challenging the traditional dominance of banks and established financial institutions. This library research study examines the multifaceted impact of fintech lending on traditional banking systems across international markets from 2015 to 2025. Through systematic analysis of academic literature, industry reports, and regulatory documentation, this research identifies five key areas of transformation: market disruption and competitive dynamics, technological innovation adoption, customer behavior evolution, regulatory framework adaptation, and risk management paradigm shifts. The findings reveal that fintech lending has created both significant challenges and opportunities for traditional financial institutions, forcing them to reimagine their business models, embrace digital transformation, and develop new competitive strategies. While fintech lenders have captured substantial market share in specific segments, particularly small business lending and consumer credit, traditional banks maintain advantages in areas requiring regulatory compliance, large-scale capital deployment, and comprehensive financial services integration. The study concludes that the future financial landscape will likely be characterized by coexistence and collaboration rather than complete displacement, with successful institutions being those that effectively integrate fintech innovations while leveraging their traditional strengths. This research contributes to the growing body of knowledge on financial services evolution and provides insights for policymakers, financial institutions, and technology companies navigating this transformative period.Keywords: Fintech lending, traditional banking, financial disruption, digital transformation, peer-to-peer lending, alternative finance